2018
DOI: 10.1093/cid/ciy722
|View full text |Cite
|
Sign up to set email alerts
|

A 9-Point Risk Assessment for Patients Who Inject Drugs and Require Intravenous Antibiotics: Focusing Inpatient Resources on Patients at Greatest Risk of Ongoing Drug Use

Abstract: A 9-point risk assessment (IVAT) identified persons with a history of injection drug use (IDU) safe for discharge. "Low risk" patients were discharged with outpatient antibiotics; others continued inpatient treatment. IVAT reduced ALOS by 20 days and total direct cost by 33%, creating capacity for an additional 333 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 6 publications
0
41
0
Order By: Relevance
“…The success rate of people with IDU-associated infective endocarditis completing their treatment with home IV antibiotics, albeit a small number of select patients in this study, suggests that further research is needed on different medical models of outpatient antibiotic therapy in this population. Thus far, the use of a risk assessment tool to guide discharge decisions has been shown to help decreased length of stays and optimize resources for individuals with ongoing IDU that may remain hospitalized [24]. While a recent study suggested noninferiority of oral antibiotics compared with intravenous antibiotics for treatment of left sided infective endocarditis, PWID were vastly underrepresented (1.3% compared to 39% in our study population) [25].…”
Section: Discussionmentioning
confidence: 99%
“…The success rate of people with IDU-associated infective endocarditis completing their treatment with home IV antibiotics, albeit a small number of select patients in this study, suggests that further research is needed on different medical models of outpatient antibiotic therapy in this population. Thus far, the use of a risk assessment tool to guide discharge decisions has been shown to help decreased length of stays and optimize resources for individuals with ongoing IDU that may remain hospitalized [24]. While a recent study suggested noninferiority of oral antibiotics compared with intravenous antibiotics for treatment of left sided infective endocarditis, PWID were vastly underrepresented (1.3% compared to 39% in our study population) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Not only are many physicians unwilling to discharge PWID home with intravenous access due to safety concerns, but practical barriers such as lack of home health services for this patient population also exist [37]. However, algorithms to identify patients who may be safely discharged home on outpatient parenteral antimicrobial therapy with central vascular catheters are now being developed [38]. The average total hospital costs for managing an episode of IE at our institution were ~$145 000, which is similar to previous studies [35].…”
Section: Discussionmentioning
confidence: 99%
“…A literature review of 10 studies on OPAT in PWID 34 found high treatment completion, low mortality, and few catheter-related complications, comparable to rates in non-PWID populations. Another study 35 implemented a 9-point tool to identify PWID candidates for OPAT, with low-risk PWID discharged to complete treatment as outpatients. Implementation resulted in reduced length of stay and cost savings without increased readmissions.…”
Section: Discussionmentioning
confidence: 99%